Pengaruh Kemampuan Kerja, Disiplin, Dan Motivasi Terhadap Kinerja Karyawan Di PT. Adi Putro Wirasejati - Kusuma, M Rafi; Khalikussabir, Khalikussabir; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2024)
AbstractÂ This research aims to determine and analyze the influence of work ability, discipline and work ability on employee performance at PT. Adiputro Wirasejati in Malang City. The population in this study are employees consisting of 4 divisions who have 5 years of work experience, namely 26 people in the machinery division, 54 people in the body repair division, 30 people in the interior division, and 15 people in the finishing division at PT. Adi Putro Wirasejati.. The data collection method in this research used a questionnaire with a sample size determined using the Slovin formula and the results obtained were 95 respondents. Data testing techniques used in this research include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, f test, t test, and coefficient of determination test (Adjusted R2). The results of this research simultaneously show that the influence of work ability, discipline, and motivation influences employee performance. Partially, Work Ability, Discipline and Motivation influence employee performance.Â Keywords: Work Ability, Discipline, Motivation and Employee Performance..